Small high-voltage nickel-metal hydride battery device and preparation process thereof
Through the design of gradient hydrophobic layer and optimization of low platinum catalyst system, the problems of high cost, poor stability and low gas mass transfer efficiency of high-pressure nickel-hydrogen batteries are solved, and the overall improvement of battery performance and safety enhancement are achieved.
Patent Information
- Application Number
- CN202510415679.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-03
- Publication Date
- 2025-07-18
AI Technical Summary
The negative electrode catalyst of traditional high-voltage nickel-hydrogen batteries is expensive, has insufficient cycle stability, and low gas mass transfer efficiency, resulting in rapid attenuation of battery capacity and increased safety risks.
The gradient hydrophobic layer design and low platinum catalyst system are adopted to construct a gradient hydrophobic structure on the negative electrode surface, combined with electrolyte modification and process optimization, the gas diffusion path and electrolyte distribution are optimized to achieve three-phase equilibrium of the reaction interface site.
It significantly reduces battery costs, improves catalytic reaction efficiency and battery performance, extends service life, reduces the problem of uneven electrolyte infiltration, and improves the stability and safety of the battery.
Smart Images

Figure CN120341295A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to the technical field of electrochemical energy storage, and particularly to a small high-voltage nickel-metal hydride battery device and a preparation process thereof. Background Art
[0002] High-voltage nickel-metal hydride batteries have natural technical advantages in the fields of energy storage devices for solar and wind energy, aviation batteries, etc. due to their high energy density, small memory effect, overcharge and over-discharge resistance, long cycle life, strong temperature adaptability, high charging efficiency, etc. However, traditional high-voltage nickel-metal hydride batteries still have certain technical defects in practical applications, which limit their further development and large-scale application.
[0003] Firstly, the negative electrode catalyst of traditional high-voltage nickel-metal hydride batteries is costly. The negative electrode usually adopts noble metal catalysts with a high platinum loading (≥20 wt%) to achieve efficient hydrogen adsorption and desorption reactions. However, precious metals such as platinum are scarce and expensive, resulting in an increase in the manufacturing cost of the battery and making it difficult to meet the requirements of large-scale commercial applications. Secondly, the cycle stability of traditional nickel-metal hydride batteries is insufficient. During long-term charge and discharge processes, the electrode active substances in the non-high platinum loading catalyst system are prone to dissolution, leading to a rapid decline in the battery capacity, and the decay rate usually exceeds 5% / 1000 cycles. At the same time, the electrolyte may dry out during the cycle, further exacerbating the degradation of the battery performance and seriously affecting the service life and stability of the battery. In addition, the gas mass transfer efficiency of traditional nickel-metal hydride batteries is low. The negative electrode will be accompanied by a hydrogen evolution reaction during charging, resulting in uneven infiltration of the electrolyte, thereby reducing the reaction kinetic efficiency. The limited gas mass transfer not only affects the charge and discharge performance of the battery but also may cause an increase in the internal pressure of the battery, increasing potential safety hazards.
[0004] Therefore, there is an urgent need to provide a nickel-metal hydride battery device with low cost and high stability. Summary of the Invention
[0005] In view of this, in order to at least partially solve at least one of the above-mentioned technical problems, the present disclosure provides a small high-voltage nickel-metal hydride battery device and a preparation process thereof.
[0006] According to an embodiment of one aspect of the present disclosure, a negative electrode for a nickel-metal hydride battery is provided. The negative electrode sequentially includes a current collector layer, a microporous diffusion layer, and a catalytic layer stacked on top of each other, wherein the content of the hydrophobic polymer on the catalytic layer is less than the content of the hydrophobic polymer on the microporous diffusion layer.
[0007] According to an embodiment of another aspect of the present disclosure, a preparation method of the above-mentioned negative electrode for a nickel-metal hydride battery is provided, including the following steps:
[0008] Add a hydrophobic polymer with a proportion of 1-5 wt% to the carbon material to obtain a microporous diffusion layer material, and spray the microporous diffusion layer material on the current collector layer to form a microporous diffusion layer;
[0009] Add a hydrophobic polymer to the platinum-based catalyst, and the ratio of the hydrophobic polymer to the platinum-based catalyst is (0.1-1):100 to obtain a modified catalyst;
[0010] Spray the modified catalyst on the microporous diffusion layer to form a catalyst layer, and obtain a negative electrode for a nickel-metal hydride battery.
[0011] According to an embodiment of the third aspect of the present disclosure, a nickel-metal hydride battery is provided, including a positive electrode, the negative electrode for the nickel-metal hydride battery described above, a negative electrode-current collector, a separator, and an electrolyte. The negative electrode-current collector includes a hydrophobic polymer and nickel foam. The separator is located between the negative electrode and the positive electrode. The negative electrode-current collector is disposed on the side of the negative electrode away from the separator. The electrolyte infiltrates into the voids between the separator and the positive electrode and the negative electrode, and infiltrates the positive electrode material.
[0012] According to an embodiment of the fourth aspect of the present disclosure, a preparation process of the above nickel-metal hydride battery is provided, including:
[0013] Place the separator between the positive and negative electrodes for assembly to obtain a battery assembly;
[0014] Perform a vacuum treatment on the battery assembly to make the gas pressure in the battery assembly less than 0.1 atmosphere, inject the electrolyte and hydrogen at 1-8 Mpa, and seal to obtain a pretreated nickel-metal hydride battery;
[0015] Perform a formation treatment on the pretreated nickel-metal hydride battery to obtain a nickel-metal hydride battery.
[0016] According to an embodiment of the present disclosure, a negative electrode for a nickel-metal hydride battery is provided. By adjusting the content of the hydrophobic polymer in the microporous diffusion layer and the catalyst layer, a gradient hydrophobic negative electrode is constructed, so that the hydrophobicity of the negative electrode surface gradually changes from the outside to the inside. The low hydrophobicity of the outer layer is conducive to the initial adsorption and diffusion of hydrogen, and the high hydrophobicity of the inner layer prevents excessive infiltration of the electrolyte, ensuring efficient hydrogen transmission. At the same time, the microporous diffusion layer provides a physical channel and enhances the interaction between hydrogen and the material surface. The three-phase balance of the reaction interface sites is achieved, the catalytic reaction efficiency is improved, the problem of uneven electrolyte infiltration is reduced, and the performance and service life of the battery are significantly improved. Description of the Drawings
[0017] Figure 1 It is a schematic structural diagram of the nickel-metal hydride battery of the present disclosure;
[0018] Figure 2 It is a comparison diagram of the surface of the microporous diffusion layer of the nickel-metal hydride battery in Embodiment 1 and Comparative Example 3 of the present disclosure;
[0019] Figure 3 is a graph showing the capacity retention rate of the nickel-hydrogen battery in Example 1 of the present disclosure as a function of the number of charge and discharge cycles;
[0020] Figure 4 This is a graph showing the capacity retention rate of the nickel-hydrogen battery in comparative example 5 of the present disclosure as a function of the number of charge and discharge cycles. DETAILED DESCRIPTION
[0021] In order to make the objectives, technical solutions and advantages of the present disclosure more clearly understood, the present disclosure is further described in detail below in conjunction with specific embodiments.
[0022] The endpoints and any values of the ranges disclosed in this disclosure are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, and these numerical ranges should be regarded as specifically disclosed in this disclosure.
[0023] The terms used herein are only for describing specific embodiments and are not intended to limit the present disclosure. The terms "comprise", "include", etc. used herein indicate the existence of the features, steps, operations and / or components, but do not exclude the existence or addition of one or more other features, steps, operations or components.
[0024] High-voltage nickel-hydrogen batteries have shown great potential in the field of energy storage and conversion due to their high energy density, small memory effect, resistance to overcharge and discharge, long cycle life, strong temperature adaptability, and high charging efficiency. However, traditional nickel-hydrogen batteries have some problems that need to be solved, such as the high cost of negative electrode catalysts, the easy dissolution of electrode active substances, which leads to rapid battery capacity decay and poor battery stability. In addition, the gas mass transfer efficiency of traditional nickel-hydrogen batteries is low, and the hydrogen evolution reaction accompanying the negative electrode during the charging and discharging process will cause uneven electrolyte infiltration, thereby reducing the reaction kinetic efficiency. Limited gas mass transfer not only affects the charging and discharging performance of the battery, but may also cause the internal pressure of the battery to increase, increase safety hazards, and limit its application in long-cycle energy storage scenarios.
[0025] Based on this, the present disclosure proposes a small high-pressure nickel-metal hydride battery device and its preparation process. Through the synergistic coupling of gradient hydrophobic layer design, low-platinum catalytic system, electrolyte modification, and process optimization, the battery performance is systematically improved. Specifically, a gradient hydrophobic layer is constructed on the negative electrode surface, making the hydrophobicity of the negative electrode surface gradually change from the outside to the inside. While providing a physical channel for gas, it significantly enhances the interaction between hydrogen and the material surface, achieves the three-phase balance of reaction interface sites, greatly improves the catalytic reaction efficiency, effectively reduces the problem of uneven electrolyte infiltration, and thus significantly improves the battery performance and service life. On this basis, through the synergistic effect of loading a low-platinum catalyst (platinum content less than 4 wt%) and modifying the electrolyte wettability, the utilization rate of catalytic active sites is improved while reducing costs, further enhancing the overall performance of the battery. During the preparation process, the vacuum injection method is adopted to ensure the uniform distribution of the electrolyte, further optimizing the battery performance. Through the optimization and coordination of each structure of the battery, the prepared nickel-metal hydride battery has significant advantages such as cost reduction, capacity improvement, and reduced capacity decay, providing new technical means and methods for the development of the energy storage field.
[0026] According to an embodiment of one aspect of the present disclosure, a negative electrode for a nickel-metal hydride battery is provided. The negative electrode sequentially includes a current collector layer, a microporous diffusion layer, and a catalytic layer in an overlapping manner, wherein the content of the hydrophobic polymer on the catalytic layer is less than the content of the hydrophobic polymer on the microporous diffusion layer.
[0027] According to an embodiment of the present disclosure, a negative electrode for a nickel-metal hydride battery with a gradient hydrophobic structure is provided. By adjusting the content of the hydrophobic polymer in the microporous diffusion layer and the catalytic layer, a gradient hydrophobic negative electrode is constructed, and the hydrophobicity on the negative electrode side gradually changes in a gradient manner from the current collector layer, the microporous diffusion layer to the catalytic layer. Specifically, the current collector layer, as a highly hydrophobic region, is conducive to the initial adsorption and diffusion of gaseous hydrogen, providing a convenient channel for hydrogen to enter the electrode interior. The microporous diffusion layer is a moderately hydrophobic region, which can effectively block the infiltration of the electrolyte and ensure the efficient transmission of hydrogen inside the electrode. The catalyst has relatively low hydrophobicity and can effectively form a large number of three-phase catalytic sites, further improving the mass transfer adsorption and reaction efficiency of hydrogen. This gradient hydrophobic design achieves the dynamic balance of the solid-liquid-gas three-phase interface, optimizes the distribution of reaction interface sites, and significantly improves the catalytic reaction efficiency. At the same time, it solves the problems of excessive or insufficient electrolyte infiltration, reduces the occurrence of insufficient three-phase sites, uneven reaction environment, electrode polarization, and side reactions, and realizes the comprehensive improvement of the performance of high-pressure nickel-metal hydride batteries.
[0028] According to an embodiment of the present disclosure, the microporous diffusion layer includes a hydrophobic polymer and a carbon material, and the hydrophobic polymer is selected from any one of polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, and polypropylene. The hydrophobic polymer is used to improve the hydrophobicity of nickel foam and effectively block the penetration and infiltration of the electrolyte or moisture, thereby enhancing the electrode stability. The carbon material can be, for example, common commercial activated carbon. The ratio of the hydrophobic polymer to the carbon material is (1 to 5):100, and can be, for example, 1:100, 2:100, 3:100, 4:100, 5:100, etc. The contact angle of the microporous diffusion layer with respect to the aqueous phase reagent is greater than 90 degrees. The pore size of the microporous diffusion layer is less than 2 nm, and can be, for example, 2 nm, 1.5 nm, 1 nm, 0.5 nm, etc.
[0029] The catalytic layer includes a hydrophobic polymer and a platinum-based catalyst. The platinum-based catalyst is a carbon-based platinum-ruthenium-nickel ternary alloy catalyst, wherein the proportion of platinum is 2 to 4 wt%, the proportion of ruthenium is 1 to 3 wt%, and the proportion of nickel is 1 to 3 wt%. For example, the proportion of platinum can be 2 wt%, 2.5 wt%, 3 wt%, 3.5 wt%, 4 wt%, etc., the proportion of ruthenium can be 1 wt%, 1.5 wt%, 2 wt%, 2.5 wt%, 3 wt%, etc., and the proportion of nickel can be 1 wt%, 1.5 wt%, 2 wt%, 2.5 wt%, 3 wt%, etc. The present disclosure adopts a low-platinum loading catalyst with a platinum proportion ≤ 4 wt%. The catalytic activity and corrosion resistance are significantly improved through the synergistic effect of ruthenium and nickel. Compared with the commonly used platinum-based catalyst, the platinum consumption of the platinum-based catalyst of the present disclosure can be relatively reduced by 80%, and the comprehensive cost can be reduced by 40%. Exemplarily, the platinum-based catalyst of the present disclosure can control the composition of the composite catalyst through an impregnation-sintering method, thereby optimizing the performance of the catalyst, further reducing the platinum consumption, and improving the resource utilization efficiency and economic benefits. The ratio of the hydrophobic polymer to the platinum-based catalyst is (0.1 to 1):100, and can be, for example, 0.1:100, 0.3:100, 0.5:100, 0.7:100, 1:100, etc.
[0030] The current collector layer includes a hydrophobic carbon material, which is selected from any one of modified or unmodified carbon paper, carbon felt, and graphite felt. The hydrophobic carbon material has good electrical conductivity and chemical stability, can effectively reduce the internal resistance of the battery, improve the charge and discharge efficiency and cycle stability of the battery. Its hydrophobicity can effectively prevent excessive penetration of the electrolyte, reduce the corrosion and dissolution of the electrode material, and extend the battery life.
[0031] According to an embodiment of the present disclosure, the contact angle of the current collector layer of the negative electrode with respect to the aqueous solvent is greater than 120°, for example, it can be 125°, 130°, 135°, 140°, 150°, etc., the contact angle of the microporous diffusion layer with respect to the aqueous solvent is greater than 90°, for example, it can be 90°, 100°, 110°, 120°, 125°, etc., and the contact angle of the catalyst layer with respect to the aqueous solvent is greater than 30°, for example, it can be 35°, 40°, 45°, 50°, etc.
[0032] According to an embodiment of another aspect of the present disclosure, a method for preparing the above-mentioned negative electrode is provided, including the following steps:
[0033] Add a hydrophobic polymer with a proportion of 1-5 wt% to the carbon material to obtain a microporous diffusion layer material, and coat the microporous diffusion layer material on the current collector layer to form the microporous diffusion layer;
[0034] Add a hydrophobic polymer to the platinum-based catalyst, and the ratio of the hydrophobic polymer to the platinum-based catalyst is (0.1-1):100 to obtain a modified catalyst;
[0035] Spray the modified catalyst on the microporous diffusion layer to form a catalyst layer, and obtain a negative electrode for a nickel-metal hydride battery.
[0036] According to an embodiment of the present disclosure, by using hydrophobic polymers with different concentrations to hydrophobically modify the microporous diffusion layer and the catalyst layer, a negative electrode with a stepped hydrophobic structure is constructed. Thereby optimizing the gas diffusion path and electrolyte distribution, while improving the catalyst performance, significantly enhancing the charge and discharge efficiency, cycle stability, and overall performance of the nickel-metal hydride battery.
[0037] According to an embodiment of still another aspect of the present disclosure, a nickel-metal hydride battery is provided, including a positive electrode, a negative electrode, a negative electrode current collector, a separator, and an electrolyte. Among them, the negative electrode includes the above-mentioned negative electrode for a nickel-metal hydride battery, the negative electrode current collector includes a hydrophobic polymer and nickel foam, the separator is located between the negative electrode and the positive electrode, the negative electrode current collector is provided on the side of the negative electrode away from the separator, and the electrolyte infiltrates the voids between the separator and the positive electrode and the negative electrode and fully infiltrates the positive electrode material.
[0038] According to an embodiment of the present disclosure, a negative electrode with a stepped hydrophobic structure is used to match it with the positive electrode and the separator to construct a nickel-metal hydride battery. The negative electrode with a stepped hydrophobic structure can optimize the gas diffusion path and electrolyte distribution, effectively reduce the electrode polarization phenomenon, thereby significantly enhancing the charge and discharge efficiency, cycle stability, and partial capacitance of the battery, meeting the key requirements of high-performance batteries in practical applications.
[0039] Figure 1 It is a schematic structural diagram of the nickel-metal hydride battery of the present disclosure.
[0040] As Figure 1As shown in the figure, the nickel-metal hydride battery includes a positive electrode 3, a separator 4, a negative electrode 5, and a negative electrode-current collector 6. The separator 4 is located between the positive electrode 3 and the negative electrode. The negative electrode-current collector 6 is disposed on the side of the negative electrode away from the separator 4. Sealing rings 2 and gaskets 7 are respectively provided on both sides of the positive electrode 3 and the negative electrode to ensure the sealing inside the battery and prevent the leakage of the electrolyte. Two battery cases 1 are used for assembly and fastened by bolts 10 to obtain a battery assembly. The battery assembly is subjected to operations such as vacuum pumping, electrolyte injection, and hydrogen injection through a pipeline 8. During the operation process, the change in the internal pressure of the battery is observed through a pressure gauge 9.
[0041] According to an embodiment of the present disclosure, the method for preparing the negative electrode-current collector includes: soaking nickel foam in a hydrophobic polymer emulsion with a concentration of 1% to 5%, and heating and curing at 300 to 350 °C for 0.2 to 1 h in an inert gas environment to obtain the negative electrode-current collector. The heating and curing temperature is 300 to 350 °C, for example, it can be 300 °C, 310 °C, 320 °C, 330 °C, 340 °C, 350 °C, etc., and the curing time is 0.2 to 1 hour, for example, it can be 0.2 hour, 0.5 hour, 0.7 hour, 0.9 hour, 1 hour, etc. Suitable curing temperature and curing time can ensure good bonding between the hydrophobic polymer and nickel foam, ensure uniform curing of the microporous diffusion layer, and at the same time avoid the decline of material performance caused by too high temperature, and improve the firmness of the interlayer bonding. In addition, the three-dimensional network structure of nickel foam provides a large specific surface area and excellent electrical conductivity.
[0042] According to an embodiment of the present disclosure, the electrolyte includes 25 to 32 wt% of potassium hydroxide, 0.2 to 3 wt% of lithium hydroxide, and 2 to 4 wt% of ethylene glycol. For example, potassium hydroxide can be 25 wt%, 27 wt%, 29 wt%, 30 wt%, 32 wt%, etc., lithium hydroxide can be 0.2 wt%, 0.5 wt%, 1 wt%, 1.5 wt%, 2 wt%, 2.5 wt%, 3 wt%, etc., and ethylene glycol can be 2 wt%, 2.5 wt%, 3 wt%, 3.5 wt%, 4 wt%, etc. Among them, ethylene glycol as a wetting agent can effectively improve the utilization rate of the positive electrode. By improving the wettability of the electrolyte to the positive electrode material, it promotes the transmission and reaction of ions, thereby improving the overall performance of the battery. Lithium ions (Li + ) in lithium hydroxide can adsorb on the surface of the positive nickel hydroxide active material, effectively preventing the growth and coalescence of the active material, thereby improving the utilization rate of the electrode active material. Lithium ions can also prevent the expansion of the electrode during charge and discharge, enhance the reversibility of the electrode reaction, and are beneficial to maintaining the stability of the battery and extending the service life. In addition, lithium ions can also strengthen the oxygen evolution polarization during the charging process of the electrode, further extending the service life of the electrode. By optimizing the electrolyte formula and the proportion of each component, the optimization of the electrolyte performance is achieved, providing a guarantee for the efficient operation and long-term stability of the nickel-metal hydride battery.
[0043] According to an embodiment of the present disclosure, the positive electrode includes nickel hydroxide active material and an in-built nickel current collector. In practical applications, for example, nickel hydroxide, nickel foam, and polyvinylidene fluoride can be used as the positive electrode. The nickel hydroxide active material can provide the electrode electro-chemical reaction ability. The nickel foam serves as the in-built nickel current collector, and polyvinylidene fluoride serves as a binder to enhance the structural stability of the positive electrode. During frequent charge and discharge processes, the nickel hydroxide active material is prone to dissolution, resulting in a decline in electrode performance. By using binders such as polyvinylidene fluoride, this dissolution can be effectively inhibited, thereby extending the service life of the positive electrode and improving the cycle stability and reliability of the battery.
[0044] According to an embodiment of the present disclosure, the separator is a hydrophilic polymer separator. In practical applications, a sulfonated polypropylene grafted membrane with a sulfonic acid group content of 0.5 - 1.2 mmol / g can be specifically selected. The sulfonated polypropylene grafted membrane has a high liquid absorption rate (≥70 mm / 10min), which can accelerate the battery formation process, balance the charge and discharge cycles, and effectively assist in the thermal management of the battery cell. An adequate liquid absorption amount (≥500 g / m²) can significantly reduce the internal resistance of the battery cell and simultaneously slow down the heating of the battery cell, improving the thermal stability of the battery. In addition, its high mechanical tensile strength (tensile strength > 100 N / 5cm) can effectively prevent short-circuit phenomena caused by pressing inside the battery cell, thus ensuring the safety and reliability of the battery and providing guarantee for the efficient operation and long-term stability of the battery.
[0045] According to an embodiment of the present disclosure, the capacity of the nickel-metal hydride battery is 200 - 1000 mAh. For example, it can be 200 mAh, 500 mAh, 700 mAh, 900 mAh, 1000 mAh, etc. After 1500 cycles, the capacity attenuation is ≤2%. For example, the capacity attenuation is 2%, 1.5%, 1.3%, 1%, 0.5%, etc. The nickel-metal hydride battery of the present disclosure has good capacitance and cycle stability. The charge and discharge rate of the nickel-metal hydride battery is 0.1 - 0.5 C, specifically it can be 0.1 C, 0.2 C, 0.3 C, 0.4 C, 0.5 C, etc. This rate range ensures the stability and efficiency of the battery during charge and discharge processes and simultaneously extends the service life of the battery. Based on this structure, series and parallel connections to achieve capacity improvement are still within the protection scope of this patent.
[0046] According to an embodiment of another aspect of the present disclosure, a preparation process of the above nickel-metal hydride battery is provided, including:
[0047] Placing the separator between the positive and negative electrodes for assembly to obtain a battery assembly;
[0048] The battery assembly is subjected to a vacuum treatment to make the gas pressure in the battery assembly less than 0.1 atmospheres, and then electrolyte and hydrogen gas at 1-8 Mpa are injected in sequence. After sealing, a pre-treated nickel-metal hydride battery is obtained;
[0049] The pre-treated nickel-metal hydride battery is subjected to a forming treatment to obtain a nickel-metal hydride battery.
[0050] According to an embodiment of the present disclosure, during the preparation process of the nickel-metal hydride battery, through vacuum treatment and control of the hydrogen gas pressure, the internal environment of the battery is ensured to be stable, and the gas diffusion and electrolyte distribution are optimized, thereby improving the charge and discharge efficiency and capacity retention rate of the battery, and preparing a high-pressure (1-8 Mpa) nickel-metal hydride battery with high stability and energy density.
[0051] According to an embodiment of the present disclosure, the battery assembly is fastened by bolts, and the bolt torque range can be preferably 5-8 N·m to ensure the tightness of each contact interface and the sealing of the assembly. At the same time, ensure that the interface contact resistance is less than 5 mΩ, reduce the internal resistance of the battery, and improve the charge and discharge efficiency of the battery.
[0052] According to an embodiment of the present disclosure, during the assembly process of the nickel-metal hydride battery, it can be set as a single-layer nickel-metal hydride battery or a multi-layer nickel-metal hydride battery according to actual needs. This flexible structural design can meet the requirements of different application scenarios for battery capacity and size, and improve the versatility and applicability of the battery.
[0053] According to an embodiment of the present disclosure, the forming treatment includes: at a temperature of 40-60 °C, the pre-treated nickel-metal hydride battery is cyclically charged and discharged 5-10 times at a rate of 0.025C-0.1C, and the charging and discharging time for each time is 2-10 hours to obtain a nickel-metal hydride battery. In the actual operation process, specifically, at 40-60 °C, it can be cyclically charged and discharged 5 times at a rate of 0.1C: charging for 2 hours and discharging for 2 hours, charging for 4 hours and discharging for 4 hours, charging for 6 hours and discharging for 6 hours, charging for 8 hours and discharging for 8 hours, charging for 10 hours and discharging for 10 hours to complete the forming process. By performing the forming treatment within the temperature range of 40-60 °C, for example, at temperatures such as 40 °C, 45 °C, 50 °C, 55 °C, 60 °C, etc., an appropriate temperature can effectively activate the positive and negative electrode materials of the battery, form a stable passivation film on the electrode surface, and improve the activity and reaction efficiency of the electrode. The forming process of gradually increasing the charge and discharge time can enable the active substances inside the battery to fully participate in the reaction, make the electrode reaction inside the battery more uniform and stable, reduce the phenomenon of local overcharging or over-discharging, and thus improve the initial capacity and subsequent cycle capacity of the battery.
[0054] The following lists multiple specific embodiments to illustrate the technical solutions of the present invention in detail. It should be noted that the specific embodiments below are only for illustration and do not limit the present invention.
[0055] Example 1
[0056] This example provides a nickel-metal hydride battery, which includes a positive electrode, a negative electrode, a separator, and an electrolyte. The catalyst used in the nickel-metal hydride battery provided in this example is prepared by the following method:
[0057] Synthesis of negative electrode catalyst:
[0058] Take 10 g of XC-72R carbon powder, impregnate it with chloroplatinic acid (platinum content 4 wt%), ruthenium trichloride (ruthenium content 1.7 wt%), and nickel nitrate (nickel content 0.8 wt%) after pickling with nitric acid;
[0059] Sinter at 700 °C for 2 hours in a 5% hydrogen-argon atmosphere to obtain a carbon-based platinum-ruthenium-nickel ternary alloy catalyst S-1109, and the BET specific surface area of the catalyst is 635 m² / g.
[0060] Electrode preparation:
[0061] Positive electrode: Spray a 1.5 wt% solution of polyvinylidene fluoride (PVDF) on a commercial-grade nickel hydroxide slurry (specific capacity 28 mAh / cm²), and dry it at 90 °C to obtain the positive electrode of the nickel-metal hydride battery.
[0062] Negative electrode: Add 5 wt% of polytetrafluoroethylene (PTFE) to activated carbon to obtain a microporous diffusion layer material. Coating the microporous diffusion layer material on a hydrophobic carbon paper with a contact angle of 125° relative to the water solvent to form a microporous diffusion layer with a contact angle of 105° relative to the water solvent; Add PTFE to the catalyst S-1109, and the ratio of PTFE to the catalyst is 0.5:100 to obtain a modified catalyst; Spray the modified catalyst on the microporous diffusion layer to form a catalyst layer with a contact angle of 35° relative to the water solvent, and the loading is 2 mg / cm 2 , to obtain the negative electrode for the nickel-metal hydride battery.
[0063] Preparation of negative electrode - current collector:
[0064] Soak the nickel foam in a 5% concentration of PTFE emulsion for 30 minutes and then take it out, and cure it in a nitrogen atmosphere at 340 °C for 1 hour to obtain a negative electrode - current collector material with a contact angle of 95° relative to the water solvent.
[0065] Battery assembly:
[0066] Stack the positive electrode with an area of 10 cm 2 , the SK-20 separator, the negative electrode, and the negative electrode current collector in sequence. Place the battery case at both ends of the stacked electrodes and separators, and tighten it with bolts at a torque of 6 N·m to obtain a battery assembly;
[0067] The battery assembly is evacuated so that the gas pressure in the battery assembly is less than 0.1 atmospheres. An electrolyte of 30 wt% potassium hydroxide (KOH) + 1.5 wt% lithium hydroxide (LiOH) + 2 wt% ethylene glycol is injected, and then hydrogen gas at 8 Mpa is injected. After maintaining the pressure for 24 hours, a pre-treated nickel-metal hydride battery is obtained;
[0068] Under the condition of 40~60 °C, the pre-treated nickel-metal hydride battery is cycled for charge and discharge 5 times at a rate of 0.1C: charge for 2 hours and discharge for 2 hours, charge for 4 hours and discharge for 4 hours, charge for 6 hours and discharge for 6 hours, charge for 8 hours and discharge for 8 hours, charge for 10 hours and discharge for 10 hours. After the formation process, nickel-metal hydride battery 1 is obtained.
[0069] Example 2
[0070] This example provides a nickel-metal hydride battery, which is different from Example 1 in that:
[0071] The microporous diffusion layer material is coated on a hydrophobic carbon paper with a contact angle of 135° relative to the water solvent. The remaining steps are the same as those in Example 1, and nickel-metal hydride battery 2 is prepared.
[0072] Example 3
[0073] This example provides a nickel-metal hydride battery, which is different from Example 1 in that:
[0074] 3 wt% of PTFE is added to the activated carbon to obtain the microporous diffusion layer material. The microporous diffusion layer material is coated on a hydrophobic carbon paper with a contact angle of 125° relative to the water solvent to form a microporous diffusion layer with a contact angle of 95° relative to the water solvent. The remaining steps are the same as those in Example 1, and nickel-metal hydride battery 3 is prepared.
[0075] Example 4
[0076] This example provides a nickel-metal hydride battery, which is different from Example 1 in that:
[0077] PTFE is added to the catalyst S-1109, and the ratio of PTFE to the catalyst is 1:100 to obtain a modified catalyst; the modified catalyst is sprayed on the microporous diffusion layer to form a catalyst layer with a contact angle of 50° relative to the water solvent. The remaining steps are the same as those in Example 1, and nickel-metal hydride battery 4 is prepared.
[0078] Example 5
[0079] This example provides a nickel-metal hydride battery, which is different from Example 1 in that:
[0080] Negative electrode - current collector preparation:
[0081] The nickel foam was immersed in a 3% PTFE emulsion for 30 min and then taken out, and cured in a nitrogen atmosphere at 340 °C for 1 h to obtain a negative electrode - current collector material with a contact angle of 100° relative to the aqueous solvent. The remaining steps were the same as those in Example 1, and a nickel - hydrogen battery 5 was prepared.
[0082] Comparative Example 1
[0083] This comparative example provides a nickel - hydrogen battery, which is different from Example 1 in that:
[0084] Negative electrode: A ruthenium - nickel catalyst was loaded on the microporous diffusion layer (the difference from the catalyst in Comparative Example 1 is that no platinum salt was added, and other conditions are the same). A nickel - hydrogen battery 6 was prepared.
[0085] Comparative Example 2
[0086] This comparative example provides a nickel - hydrogen battery, which is different from Example 1 in that:
[0087] A high - platinum - loading catalyst was loaded on the microporous diffusion layer. The high - platinum - loading catalyst is commercial platinum - carbon with a platinum proportion of 20 wt%. A nickel - hydrogen battery 7 was prepared.
[0088] Comparative Example 3
[0089] This comparative example provides a nickel - hydrogen battery, which is different from Example 1 in that:
[0090] The nickel foam without PTFE hydrophobization treatment was used as the negative electrode - current collector, and directly adhered to the S - 1109 catalyst to prepare a nickel - hydrogen battery 8.
[0091] Figure 2 This is a surface comparison diagram of the microporous diffusion layer of the nickel - hydrogen batteries in Example 1 and Comparative Example 3 of the present disclosure.
[0092] As Figure 2 shown, in Example 1, the nickel foam surface was treated with PTFE. PTFE has good hydrophobicity, so the surface of the treated nickel foam shows obvious hydrophobic characteristics, which helps to form a stable gas - liquid interface on the electrode surface, promotes gas diffusion and uniform distribution of the electrolyte, thereby improving the performance and stability of the battery. In Comparative Example 3, the nickel foam surface was not treated with PTFE hydrophobization, so its surface shows hydrophilicity. The hydrophilic surface is easily wetted in the electrolyte, which may lead to excessive adsorption of the electrolyte, thus affecting gas diffusion and the reaction efficiency of the electrode.
[0093] Comparative Example 4
[0094] This comparative example provides a nickel - hydrogen battery, which is different from Example 1 in that:
[0095] A high-platinum-loading catalyst is loaded on the microporous diffusion layer, and the proportion of platinum in the high-platinum-loading catalyst is 8 wt%. A nickel-metal hydride battery 9 is prepared.
[0096] Comparative Example 5
[0097] This comparative example provides a nickel-metal hydride battery, which is different from Example 1 in that:
[0098] The electrolyte is 30% KOH + 1.5% LiOH and does not contain ethylene glycol. A nickel-metal hydride battery 10 is prepared.
[0099] Comparative Example 6
[0100] This comparative example provides a nickel-metal hydride battery, which is different from Example 1 in that:
[0101] Negative electrode: The contact angles of the catalytic layer, the microporous diffusion layer, and the current collector layer with respect to the aqueous solvent are all 100°. A nickel-metal hydride battery 11 is prepared.
[0102] The nickel-metal hydride batteries in Examples 1 to 5 and Comparative Examples 1 to 6 of the present disclosure are subjected to electrochemical performance tests, and the specific test results are shown in Table 1.
[0103] Table 1
[0104]
[0105] For the nickel-metal hydride batteries of Examples 1 to 5, at a discharge rate of 0.1C, the discharge capacity of the nickel-metal hydride battery can reach more than 276 mAh. After 1500 charge-discharge cycles, the capacity retention rate of the battery reaches more than 98.5%, showing good cycle stability.
[0106] For the nickel-metal hydride battery 6 in Comparative Example 1, at a discharge rate of 0.1C, the discharge capacity is 273 mAh. After 1000 charge-discharge cycles, the attenuation rate of the battery is 7%. The electrochemical performance of the nickel-metal hydride batteries using low-loading platinum-based catalysts in Examples 1 to 5 is superior to that of the nickel-metal hydride batteries using ruthenium-nickel catalysts. This is because although the platinum content in the low-platinum-loading catalyst is relatively low, the synergistic effect of platinum, ruthenium, and nickel therein can significantly improve the catalytic performance.
[0107] After 1000 charge-discharge cycles, the capacity attenuation of the nickel-metal hydride batteries in Comparative Examples 2 to 3 is significantly lower than that in Examples 1 to 5.
[0108] The initial capacity of the nickel-metal hydride battery 9 in Comparative Example 4 is 275 mAh, which is similar to the capacity of the nickel-metal hydride battery 1 in Example 1. After 500 cycles, the capacity attenuation is 2.5%, and there is no significant difference in performance. However, the proportion of precious metal platinum used in Comparative Example 4 is relatively high, and the cost increases by nearly 200%.
[0109] Figure 3It is a graph showing the change of the capacity retention rate of the nickel-metal hydride battery in Embodiment 1 of the present disclosure with the number of charge-discharge cycles; Figure 4 It is a graph showing the change of the capacity retention rate of the nickel-metal hydride battery in Comparative Example 5 of the present disclosure with the number of charge-discharge cycles.
[0110] As shown in Table 1, Figure 3 and Figure 4 After the nickel-metal hydride battery 10 in Comparative Example 5 was charged and discharged 1500 times, the capacity retention rate decreased significantly compared with that of the nickel-metal hydride battery 1 in Embodiment 1. The initial capacity of the nickel-metal hydride battery 10 in Comparative Example 5 was 240 mAh, which was 14% lower than the capacity of the nickel-metal hydride battery 1 in Embodiment 1, and the capacity decayed by 2.5% after 1500 cycles.
[0111] The initial capacity of the nickel-metal hydride battery 11 in Comparative Example 6 without using a gradient water-transporting negative electrode was 232 mAh, and the capacity decayed by 16% after 500 cycles.
[0112] Therefore, the present disclosure solves the problems of high catalyst cost and poor cycle stability of traditional nickel-metal hydride batteries through processes such as the synergistic optimization of platinum-based catalysts, hydrophobic electrode structures, and electrolytes.
[0113] The specific embodiments described above have further elaborated on the purpose, technical solutions, and beneficial effects of the present disclosure. It should be understood that the above are only specific embodiments of the present disclosure and are not used to limit the present disclosure. Any modifications, equivalent replacements, improvements, etc. made within the spirit and principle of the present disclosure shall be included within the protection scope of the present disclosure.
Claims
1. A negative electrode for a nickel-metal hydride battery, characterized in that: The negative electrode sequentially includes a current collector layer, a microporous diffusion layer, and a catalytic layer in a stacked manner. Among them, the content of the hydrophobic polymer on the catalytic layer is less than the content of the hydrophobic polymer on the microporous diffusion layer.
2. The negative electrode for a nickel-metal hydride battery according to claim 1, characterized in that: The microporous diffusion layer includes a hydrophobic polymer and a carbon material, and the ratio of the hydrophobic polymer to the carbon material is (1-5):
100. The pore size of the microporous diffusion layer is less than 2 nm. The catalytic layer includes a hydrophobic polymer and a platinum-based catalyst, and the ratio of the hydrophobic polymer to the platinum-based catalyst is (0.1-1):
100. The current collector layer includes a hydrophobic carbon material, which is any one selected from modified or unmodified carbon paper, carbon felt, and graphite felt.
3. The negative electrode for a nickel-metal hydride battery according to claim 2, characterized in that: The hydrophobic polymer is any one selected from polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, and polypropylene. The platinum-based catalyst is a carbon-based platinum-ruthenium-nickel ternary alloy catalyst, in which platinum accounts for 2-4 wt%, ruthenium accounts for 1-3 wt%, and nickel accounts for 1-3 wt%.
4. The negative electrode for a nickel-metal hydride battery according to claim 1, characterized in that: The contact angle of the catalytic layer with respect to the water solvent is greater than 30°. The contact angle of the microporous diffusion layer with respect to the water solvent is greater than 90°. The contact angle of the current collector layer with respect to the water solvent is greater than 120°.
5. A method for preparing a negative electrode for a nickel-metal hydride battery according to any one of claims 1 to 4, characterized in that, It includes the following steps: Add a hydrophobic polymer with a proportion of 1-5 wt% to the carbon material to obtain a microporous diffusion layer material, and coat the microporous diffusion layer material on the current collector layer to form the microporous diffusion layer. Add a hydrophobic polymer to the platinum-based catalyst, and the ratio of the hydrophobic polymer to the platinum-based catalyst is (0.1-1):100, to obtain a modified catalyst. Spray the modified catalyst on the microporous diffusion layer to form a catalyst layer, and obtain the negative electrode for a nickel-metal hydride battery.
6. A nickel-metal hydride battery, including a positive electrode, a negative electrode, a negative electrode-current collector, a separator, and an electrolyte, characterized in that: The negative electrode includes the negative electrode for a nickel-metal hydride battery according to any one of claims 1 to 4. The negative electrode-current collector includes a hydrophobic polymer and nickel foam. The separator is located between the negative electrode and the positive electrode. The negative electrode-current collector is arranged on the side of the negative electrode away from the separator. The electrolyte infiltrates into the voids between the separator, the positive electrode, and the negative electrode, and infiltrates the positive electrode material.
7. The nickel-metal hydride battery according to claim 6, characterized in that: The preparation method of the negative electrode-current collector includes: Soak the nickel foam in an emulsion of a hydrophobic polymer with a concentration of 1%-5%, and heat and cure it at 300-350 °C for 0.2-1 h in an inert gas environment to prepare the negative electrode-current collector.
8. The nickel-metal hydride battery according to claim 6, characterized in that: The contact angle of the negative electrode-current collector with respect to the water solvent is greater than 90°. The electrolyte includes 25-32 wt% of potassium hydroxide, 0.2-3 wt% of lithium hydroxide, and 2-4 wt% of ethylene glycol. The positive electrode includes nickel hydroxide active material and an internal nickel current collector. The separator is a hydrophilic polymer separator, the nickel-metal hydride battery has a capacity of 200 to 1000 mAh, and the capacity decay is ≤2% after 1500 cycles, and the charge-discharge rate of the nickel-metal hydride battery is 0.1 to 0.5 C.
9. A preparation process of a nickel-metal hydride battery according to any one of claims 6 to 8, characterized in that, the separator is placed between the positive and negative electrodes for assembly to obtain a battery assembly; the battery assembly is subjected to a vacuum treatment so that the gas pressure in the battery assembly is less than 0.1 atmosphere, and electrolyte and hydrogen at 1 to 8 Mpa are injected, and after sealing, a pretreated nickel-metal hydride battery is obtained; the pretreated nickel-metal hydride battery is subjected to formation treatment to obtain a nickel-metal hydride battery.
10. According to the preparation process of claim 9, characterized in that, the formation treatment includes: at a temperature of 40 to 60 °C, the pretreated nickel-metal hydride battery is cyclically charged and discharged 5 to 10 times at a rate of 0.025 C to 0.1 C, and the charge-discharge time for each time is 2 to 10 hours to obtain the nickel-metal hydride battery.